The Effect of Clan Organizational Culture on Employee Engagement in Educational Institutions - Dede Ahmad Sobari; Amedia Puspa (CV Projurnal Mitra Publikasi, 2025)
Corporate culture is critical to determining employee engagement, especially in educational institutions, where management and employees work together to achieve common goals. The effect of clan-type organizational culture on employee engagement in educational institutions is the subject of this study. It is considered relevant to create a work environment that supports the active participation of employees of clan culture, which is characterized by family values, cooperation, and caring. This quantitative study used a survey as a sample. Data were collected through distributing questionnaires to 75 employees of participating educational institutions. The relationship between variables was examined using simple linear regression data analysis method. The study showed that clan organization increases employee participation. Employee engagement is higher in workplaces where there is a strong sense of trust, open communication and teamwork. This shows how important it is for educational institutions to adopt clan principles to increase employee participation. Ultimately, this will help the organization achieve its goals.